2006
DOI: 10.1161/01.atv.0000227513.13697.ac
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Calcific Aortic Valve Disease

Abstract: Background-Over the past 10 to 15 years, calcific aortic valve disease, which includes aortic sclerosis and aortic stenosis, has come to be recognized as an active process, based on: (1) epidemiologic studies demonstrating associations of specific risk factors with increased prevalence or rate of progression of aortic valve disease; (2) identification, in valve lesions, of histopathologic features of chronic inflammation, lipoprotein deposition, renin-angiotensin system components, and molecular mediators of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(99 citation statements)
references
References 85 publications
3
94
0
1
Order By: Relevance
“…6 Although several risk factors are shared between atherosclerotic diseases and CAVD, discrepancies in their pathogenesis have also been identified. [8][9][10] These results highlight the necessity of investigating prognostic factors for incidence and progression of CAVD in Asian populations.…”
Section: Introductionmentioning
confidence: 85%
“…6 Although several risk factors are shared between atherosclerotic diseases and CAVD, discrepancies in their pathogenesis have also been identified. [8][9][10] These results highlight the necessity of investigating prognostic factors for incidence and progression of CAVD in Asian populations.…”
Section: Introductionmentioning
confidence: 85%
“…40 While some of the mechanisms involved in valve disease are similar to those in atherosclerosis, recent observations suggest anatomical, cellular, and genetic mechanisms that are unique to the aortic valve. 12,40,41 Accordingly, an improved understanding of the pathogenesis of calcific aortic valve disease requires better definition of these unique features, including the characteristics of the cell populations involved in the disease. In the present study, we identified for the first time a mesenchymal progenitor cell population in the aortic valve using rigorous quantitative assays established in the mesenchymal stem cell field.…”
Section: Discussionmentioning
confidence: 99%
“…[26,27] Bu nedenle, hastalar, sıklıkla aterosklerozun, arteriyel duvarda neden olduğu rijidite artışına bağlı gelişen, sistemik arteriyel kompliyansta azalma gibi bulgularına da sahiptirler.…”
Section: Paradoksal Düşük Akımlı Hastalar Aşağıdakiunclassified